Modern Technical Solutions for Cleaning, Disinfection and Sterilization - Svoboda, Antonín; Chalupa, Milan; Jelínek, Josef (Manufacturing Technology Journal, 2023)
Abstract: The article describes a new technical solution for ensuring efficient and inexpensive cleaning, disinfection and sterilization of production facilities and their equipment, based on the principle of gen-erating the use of ozone gas. It describes the technical solution and construction of sterilization and cleaning equipment with ozone gas and the sterilization of small objects, especially textiles contaminat-ed with various viruses, including the Covid-19 virus. The device is designed as energy-saving, structur-ally simple, with high sterilization and cleaning efficiency. The sterilization device is small in size, mo-bile and its design enables transportation in the trunk of an ordinary passenger car. The weight of the device is 14 kg. The device's ozone source is an ozone air purifier, mass-produced according to valid EU standards. The power source of the ozone purifier is an electrical source with a voltage of only 230 V and a frequency of 50 Hz. Alternatively, it is possible to use power from a safe mobile source or inverter. The operation of sterilization and cleaning device in a closed, non-ventilated area, does not endanger peo-ple's health or damage plants. The description of the construction of a technical sterilization device is focused on a specific type of device, but the stated theoretical results can be equally well used in the electrotechnical, food, medical or pharmaceutical industries and in general wherever there is a need to effectively and efficiently clean and sterilize production objects, their equipment, used materials and all other production aids means and tools.
Keywords: Sterilization of manufacturing equipment; Energy saving; COVID-19; Ozone cleaning; Ozone disinfection; Ozone generator; Mobile devices